1981
DOI: 10.1083/jcb.88.2.364
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence studies on modes of cytochalasin B and phallotoxin action on cytoplasmic streaming in Chara.

Abstract: Various investigations have suggested that cytoplasmic streaming in characean algae is driven by interaction between subcortical actin bundles and endoplasmic myosin . To further test this hypothesis, we have perfused cytotoxic actin-binding drugs and fluorescent actin labels into the cytoplasm of streaming Chara cells. Confirming earlier work, we find that cytochalasin B (CB) reversibly inhibits streaming. In direct contrast to earlier investigators, who have found phalloidin to be a potent inhibitor of movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 34 publications
4
38
0
Order By: Relevance
“…Using rhodamine-labelled phalloidin and an image intensification system Yanagida et al (1984) showed that single actin filaments could be readily visualized, in solution, by fluorescence microscopy. The flexural rigidity of actin was apparently unchanged by phalloidin binding and this parameter could be investigated with respect to the presence or absence of regulating proteins (troponin and tro- Euteneuer Kordell et al, 1987Schatten et al, 1986aMaekawa et al, 1987;Yonemura & Mabuchi, 1987;Schatten & Schatten, 1987 Henson & Schatten, 1983u & Kinoshita, 1986Tamm & Tamm, 1987Warn & Magrath, 1983Warn et al, 1984;Gutzeit, 1986Bertin et al, 1987Strome, 1986Shimizu, 1986Priess & Hirsch, 1986Parthasarathy, 1985Heslop-Harrison et al, 1986Quader et al, 1987Parke et al, 1986Tiwari et al, 1984Pierson et al, 1986;Palevitz et al, 1987;Seagull et al, 1987;Traas et al, 1987Nothnagel et al, 1984Bassi & Donini, 1984Adams & Pringle, 1984Kilmartin & Adams, 1984;Marks & Hyams, 1985Hoch & Staples, 1983Runeberg et al, 1986;Heath, 1987Naib-Majani, 1983Ishigami, 1986Ishigami et al, 1987Uyeda & Furuya, 1986Rubino et al, 1984Roos ...…”
Section: Incorporation Of Phalloidin Into Living Cellsmentioning
confidence: 98%
“…Using rhodamine-labelled phalloidin and an image intensification system Yanagida et al (1984) showed that single actin filaments could be readily visualized, in solution, by fluorescence microscopy. The flexural rigidity of actin was apparently unchanged by phalloidin binding and this parameter could be investigated with respect to the presence or absence of regulating proteins (troponin and tro- Euteneuer Kordell et al, 1987Schatten et al, 1986aMaekawa et al, 1987;Yonemura & Mabuchi, 1987;Schatten & Schatten, 1987 Henson & Schatten, 1983u & Kinoshita, 1986Tamm & Tamm, 1987Warn & Magrath, 1983Warn et al, 1984;Gutzeit, 1986Bertin et al, 1987Strome, 1986Shimizu, 1986Priess & Hirsch, 1986Parthasarathy, 1985Heslop-Harrison et al, 1986Quader et al, 1987Parke et al, 1986Tiwari et al, 1984Pierson et al, 1986;Palevitz et al, 1987;Seagull et al, 1987;Traas et al, 1987Nothnagel et al, 1984Bassi & Donini, 1984Adams & Pringle, 1984Kilmartin & Adams, 1984;Marks & Hyams, 1985Hoch & Staples, 1983Runeberg et al, 1986;Heath, 1987Naib-Majani, 1983Ishigami, 1986Ishigami et al, 1987Uyeda & Furuya, 1986Rubino et al, 1984Roos ...…”
Section: Incorporation Of Phalloidin Into Living Cellsmentioning
confidence: 98%
“…The pigment granules continue to move normally after NEM-HMM injection, presumably providing ample opportunity for the injected actomyosin inhibitor to locate its binding site on actin. These probes for actin and actomyosin have been shown to inhibit a diverse set of motility events including cytokinesis (7,22), some forms of axoplasmic transport (11,14), and cytoplasmic streaming (25,39,43). It seems improbable to us that none of them would be successful in affecting pigment transport if it were actin-or actomyosin-based.…”
Section: The Role Of Actin or Actomyosin In Pigment Granule Motilitymentioning
confidence: 99%
“…Because actin is involved in a wide variety of nonmuscle motile events (18,25,28,40) it represents a prime candidate for participation in pigment granule transport. Actin microfilaments have been identified in melanophores by heavy meromyosin decoration (27,37), but their role in pigment migration remains controversial.…”
mentioning
confidence: 99%
“…Our current understanding is based on extrapolations from studies of Characean algal cells, which have shown that microfilament bundles are composed of F-actin and play an essential role in the generation of cytoplasmic streaming (11)(12)(13)(14). This idea seems relevant to higher plants, based on studies showing that (i) microfilament bundles are present in streaming cells (5,15); (ii) the direction of streaming is parallel to the longitudinal axis of the microfilament bundles; and (iii) streaming is inhibited by cytochalasin B (5,(16)(17)(18), a drug known to affect microfilament bundles (19), by the ionophore A23187 (20), and by the chelating agent EGTA (5), chemicals known to affect the distribution of ions important to the generation of streaming in F-actin-containing systems (12).…”
mentioning
confidence: 99%